LINKING ENVIRONMENTAL MANAGEMENT SYSTEMS AND CIRCULAR ECONOMY PERFORMANCE: THE MEDIATING ROLE OF CIRCULAR ECONOMY CAPABILITIES IN INDONESIA’S COURIER SECTOR - Nasution, Nursery Alfaridi S; Octaviani, Reni Dian; Pratiwi, Sekar Widyastuti; Firdaus, Iqbal (International Conference on Vocational Business, Logistic, Accounting, Supply Chain, Tax (ICoBLAST); Vol 1, No 1 (2026): 1st ICoBLAST, 2026)
Introduction/Main Objectives: The surge in online purchases has been accompanied by a significant rise in unmanaged waste, including packaging materials, plastics, bubble wrap, tapes, and cardboard. This situation negatively impacts the environment and calls for sustainable solutions. One promising approach is the circular economy, which aims to minimize waste while maximizing the efficiency of resource utilization. This study aims to examine the effect of Environmental Management Systems (EMS) on the implementation of the circular economy among courier express parcel companies in Indonesia. Background Problems: The rapid growth of the courier industry driven by e-commerce has intensified environmental pressure. However, there remains limited understanding of how EMS contributes to environmental and financial performance through the adoption of circular economy principles. Novelty: While prior research has explored the effect of EMS on performance, few studies have empirically examined the mediating role of Circular Economy Capabilities (CEC) in service-oriented sectors such as logistics and courier companies in developing countries. This study fills that gap by testing how CEC strengthens the relationship between EMS and firm performance. Research Methods: This study employs a quantitative descriptive method. Data were collected through an online questionnaire distributed to middle and top management respondents from courier express parcel companies in Indonesia. The data were analyzed using SMART PLS to evaluate both direct and mediated relationships between variables. Findings/Results: The results reveal that EMS has a negative relationship with environmental performance; however, when mediated by CEC, this relationship becomes positive. In contrast, EMS positively affects financial performance. The findings confirm that CEC partially mediates the relationship between EMS and performance outcomes. Conclusion: Circular economy capabilities play a crucial role in enhancing the effectiveness of EMS, transforming environmental initiatives into improved performance outcomes. This highlights the importance of developing internal capabilities alongside institutional systems to achieve sustainability goals. Implementation Potential : The findings provide practical guidance for logistics and courier companies in adopting circular economy practices. Strengthening CE capabilities can help firms improve resource efficiency, reduce waste, and achieve long-term financial and environmental benefits.   Keywords : circular economy performance; circular economy capability; environmental management system; courier express parcel company. JEL Classification: (list the relevant JEL codes separated by commas, refer to https://www.aeaweb.org/jel/guide/jel.php )